2005
DOI: 10.1021/om0490785
|View full text |Cite
|
Sign up to set email alerts
|

New Single-Site Palladium Catalysts for the Nonalternating Copolymerization of Ethylene and Carbon Monoxide

Abstract: The synthesis and first examples of structurally characterized, single-site palladium complexes containing a phosphine sulfonate chelate (PSO) for the nonalternating copolymerization of ethylene and carbon monoxide are reported. Extra incorporation of ethylene up to 30% has been achieved relative to the alternating polyketone structure with modest activities. As exemplarily shown, high molecular weight random copolymers have been produced with M w ≈ 370 000, polydispersity (M w/M n ) = 2, and melting points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 39 publications
4
102
0
2
Order By: Relevance
“…[61] More recently, Rieger et al have reported the first examples of neutral Pd II complexes bearing sulfonated phosphane ligands (Scheme 3). Higher activities as well as higher insertion of extra amounts of ethene (up to 30 %) into the copolymer chain were achieved [62] when compared to the previously reported in situ copolymerisation reactions. [61] Scheme 3.…”
Section: P-o Ligands In Non-alternating Co/ethene Copolymerisationmentioning
confidence: 63%
See 1 more Smart Citation
“…[61] More recently, Rieger et al have reported the first examples of neutral Pd II complexes bearing sulfonated phosphane ligands (Scheme 3). Higher activities as well as higher insertion of extra amounts of ethene (up to 30 %) into the copolymer chain were achieved [62] when compared to the previously reported in situ copolymerisation reactions. [61] Scheme 3.…”
Section: P-o Ligands In Non-alternating Co/ethene Copolymerisationmentioning
confidence: 63%
“…[61][62][63] Rieger et al have proposed that this new polymerisation proceeds via two intertwined pathways (Scheme 4), where the same active species may switch between the production of alternating and non-alternating blocks in the same polymer chain. [62] Multiple ethene insertions are suggested to be facilitated by a stereoelectronic destabilisation of the neutral chelate to an extent that enables ethene to effectively compete with carbon monoxide for the next insertion, as previously proposed by Drent et al [61] Based on this report, it was assumed that the neutral nature of the CO-inserted 6-membered chelate could lead to a decarbonylation reaction yielding the five-membered ring complex that could then react with ethene to form a seven-membered chelate, which is proposed to open more easily and therefore facilitates the incorporation of further ethylene units. Furthermore, increasing the pressure of ethene and employing high CO/ethene gas blend ratios (1:20) statistically provides a higher probability of ethene insertion over carbon monoxide insertion.…”
Section: P-o Ligands In Non-alternating Co/ethene Copolymerisationmentioning
confidence: 99%
“…gand were then disclosed by Hearley et al, [6] Goodall et al, [7,8] Kochi et al, [9,10] Liu et al, [11] Skupov et al, [12] Luo et al, [13] Vela et al, [14] and most recently Guironnet et al [15] Among those reports, acrylate copolymerization with ethene was mentioned by Goodall, [7,8] Skupov, [12] and Guironnet. [15] These studies employ the catalyst [(oAr 2 PC 6 H 4 SO 3 )PdMe(L)] with Ar = o-OMePh, which corresponds to the ligand originally presented by Drent.…”
Section: Introductionmentioning
confidence: 99%
“…It also enabled non-alternating copolymerization of ethylene with CO [138]. Then, Rieger and Nozaki isolated Pd-phosphinesulfonate complexes having a pyridine, lutidine, or dihydrodicyclopentadienyl ligand, which also catalyze the copolymerization with high efficiency [139,140].…”
Section: Phosphinesulfonate Complexes Of Pdmentioning
confidence: 99%